Analisis Bibliometrik Trend Riset Ekonofisika dan Model Distribusi Kekayaan - Jaja Jamaludin; Irnin Agustina Dwi Astuti (UNIVERSITAS INDRAPRASTA PGRI, 2023)
This article provides a bibliometric analysis of econophysics and wealth distribution models. This study was conducted using the Google Schoolar database and identified articles related to econophysics and wealth distribution models. In addition, this article evaluates the journals that publish the most articles on econophysics and wealth distribution models and analyzes the most frequently discussed research topics. There are 166 articles with 2577 citations and 1.86 Author/year. One interesting research trend is the new econophysics, quantitative exchange of wealth and redistribution that compares the characteristics of capitalism and evaluates the distribution of wealth. Econophysics has produced innovative and empirically relevant results in at least four research areas: financial markets, growth and distribution of firms and countries, distribution of income and wealth, and transmission, resilience, and resilience of networks. In addition, the most frequently discussed research topics are wealth distribution, and agent-based models.